Cervicovaginal Bacteriology and Antibiotic Sensitivity Patterns among Women with Premature Rupture of Membranes in Mulago Hospital, Kampala, Uganda: A Cross-Sectional Study. (9th February 2017) - Musaba, Milton W.; Kagawa, Mike N.; Kiggundu, Charles; Kiondo, Paul; Wandabwa, Julius
Abstract : Background . A 2013 Cochrane review concluded that the choice of antibiotics for prophylaxis in PROM is not clear. In Uganda, a combination of oral erythromycin and amoxicillin is the 1st line for prophylaxis against ascending infection. Our aim was to establish the current cervicovaginal bacteriology and antibiotic sensitivity patterns. Methods . Liquor was collected aseptically from the endocervical canal and pool in the posterior fornix of the vagina using a pipette. Aerobic cultures were performed on blood, chocolate, and MacConkey agar and incubated at 35–37°C for 24–48 hrs. Enrichment media were utilized to culture for GBS and facultative anaerobes. Isolates were identified using colonial morphology, gram staining, and biochemical analysis. Sensitivity testing was performed via Kirby-Bauer disk diffusion and dilution method. Pearson's chi-squared (χ 2 ) test and the paired t -test were applied, at aP value of 0.05. Results . Thirty percent of the cultures were positive and over 90% were aerobic microorganisms. Resistance to erythromycin, ampicillin, cotrimoxazole, and ceftriaxone was 44%, 95%, 96%, and 24%, respectively. Rupture of membranes (>12 hrs), late preterm, and term PROM were associated with more positive cultures. Conclusion . The spectrum of bacteria associated with PROM has not changed, but resistance to erythromycin and ampicillin has increased.